Síntese e caracterização de TaC e óxido misto de tântalo e cobre nanoestruturados a partir do precursor oxálico de tântalo através de reações gás-sólido e sólido-sólido a baixa temperatura - Lima, Maria José Santos (2013)
The research and development of nanostructured materials have been growing significantly in the last years. These materials have properties that were significantly modified as compared to conventional materials due to the extremely small dimensions of the crystallites. The tantalum carbide (TaC) is an extremely hard material that has high hardness, high melting point, high chemical stability, good resistance to chemical attack and thermal shock and excellent resistance to oxidation and corrosion. The Compounds of Tantalum impregnated with copper also have excellent dielectric and magnetic properties. Therefore, this study aimed to obtain TaC and mixed tantalum oxide and nanostructured copper from the precursor of tris (oxalate) hydrate ammonium oxitantalato, through gas-solid reaction and solid-solid respectively at low temperature (1000 ° C) and short reaction time. The materials obtained were characterized by X-ray diffraction (XRD), Rietveld refinement, Scanning Electron Microscopy (SEM), Spectroscopy X-Ray Fluorescence (XRF), infrared spectroscopy (IR), thermogravimetric (TG), thermal analysis (DTA) and BET. Through the XRD analyses and the Reitiveld refinement of the TaC with S = 1.1584, we observed the formation of pure tantalum carbide and cubic structure with average crystallite size on the order of 12.5 nanometers. From the synthesis made of mixed oxide of tantalum and copper were formed two distinct phases: CuTa10O26 and Ta2O5, although the latter has been formed in lesser amounts